2019
DOI: 10.3390/jcm8081102
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Affect on Associations between Impulsivity or Resilience and Internet Gaming Disorder

Abstract: Internet gaming disorder (IGD) is a new disease proposed by the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5), and has been studied extensively in relation to depression and impulsivity. The relationship between resilience and disease has been found in a variety of addictive disorders, but studies on IGD are lacking. In this study, 71 IGD patients and 78 healthy controls (HCs) were recruited. Impulsivity, resilience, affects, and the degree of internet game addiction were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
1
6
0
4
Order By: Relevance
“…Low resilience is associated with IGD [ 7 , 14 , 22 , 36 ]. Yen et al [ 7 ] demonstrated that individuals with IGD and low resilience had more severe depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low resilience is associated with IGD [ 7 , 14 , 22 , 36 ]. Yen et al [ 7 ] demonstrated that individuals with IGD and low resilience had more severe depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the association between low resilience and IGD. Two studies have established that mood status and depression mediate the association between IGD and resilience [ 7 , 36 ]. A questionnaire study indicated that perceived stress correlated with gaming hours only among those with low resilience [ 14 ], and an interview study did not find the buffer effect of resilience on the association between stress and IGD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Riordan et al reported that negative affect has been associated with FoMO when using Facebook ( 62 ). Shin et al also reported the mediating effects of affect on the associations between personality factors and internet gaming disorder ( 63 ). In addition, envy as a specific negative affect has been shown to impact on problematic smartphone use and SNS addiction via FoMO ( 64 , 65 ).…”
Section: Introductionmentioning
confidence: 99%
“…El IGD está incluido en el Manual de Diagnóstico y Estadístico de los Trastornos Mentales, Quinta Edición (DSM-5) (American Psychiatric Association, 2018), que integra los criterios de su diagnóstico (Cai et al, 2016;Fuster et al, 2016;Jo et al, 2019;Shin et al, 2019;Zajac, Ginley y Chang, 2019), en los que hay nueve criterios de básicos (Müller et al, 2019) y cinco criterios de corte (Kim et al, 2016;Sprong et al, 2019). Además, está incluido en la undécima revisión final de la Clasificación Internacional de Enfermedades (CIE-11), entendiéndose como un código de diagnóstico (Jo et al, 2019;Wartberg, Kriston & Thomasius, 2020), siendo reconocido por primera vez en mayo de 2013 (Ji, Hsieh & Hsiao, 2016).…”
Section: Revisión De La Literaturaunclassified
“…Cada uno de ellos puede evidenciar funciones diagnósticas únicas en el desarrollo de los juegos adictivos (Pontes et al, 2019), más concretamente, aquellos que son de estrategias en tiempo real, juegos de rol y de fantasía (Eichenbaum et al, 2015). Algunos de los síntomas pueden ser la tolerancia, el ansia, modificación del estado de ánimo, la prominencia, la soledad, impulsividad (Chen et al, 2016;Du et al, 2016;Dang et al, 2019;Müller et al, 2019;Shin et al, 2019;Yen et al, 2019), alteraciones de las funciones cognitivas y sociales (Park et al, 2016), desapego (Laier, Wegmann & Brand, 2018), problemas en la regulación de emociones (Kang et al, 2018) y la falta de atención (Du et al, 2016), siendo este último un factor muy influyente en el IGD . Además, se le asocian otros síntomas como la depresión (Jeong et al, 2019, el número de horas de juego y a la negación, siendo estos dos últimos los predictores más fuerte de los síntomas (Schneider et al, 2017).…”
Section: Revisión De La Literaturaunclassified